Bio-Waste Derived Honeycomb Structured Activated Carbons as Anode Materials for Lead-Carbon Hybrid Ultracapacitors. Issue 9 (1st September 2022) - Muduli, Sadananda; Das Chakraborty, Rupan; Verma, Pramod; Martha, Surendra K.
Abstract : Lead-carbon hybrid ultracapacitors (Pb-C HUC) are the solution to the sulfation issue of lead-acid batteries. The Pb-C HUCs are of much interest due to the aqueous system with longer cycle life and higher power density. Here, honeycomb structured porous activated carbons with 1790 m 2 g −1 of surface area were synthesized from Carica papaya biowaste by chemical treatment followed by carbonization at 800 °C (PAC-800). PAC-800 composite electrode delivers a specific capacitance of 250 F g −1 at 1 Ag −1 and has 10000 stable cycle life in 4.5 M H2 SO4 . Further, a kinetic study of the PAC-800 electrode illustrates that at 2 mV s −1, they show 61% of capacitive and 39% of pseudocapacitive charge storage. Pb-C HUCs fabricated using in situ activated PbO2 sheet as cathode and PAC-800 composite electrode as anode delivers 390 F g −1 at 1 A g −1 and have 93% capacitance retention over 15000 cycles at 5 A g −1 . Further, the current Pb-C HUC results are compared with commercially available high surface area (2484 m 2 g −1 ) carbons based Pb-C HUCs. This work illustrates an easy, scalable synthesis root for biowaste carbons and their electrochemical performance in Pb-C HUCs, which is on par with commercial high surface area carbons.